Identification of stable reference genes for quantitative PCR in koalas - Sarker, N.; Fabijan, J.; Emes, Richard D.; Hemmatzadeh, F.; Meers, J.; Moreton, Joanna; Owen, H.; Seddon, J.; Simmons, G.; Speight, N.; Trott, D.; Woolford, L.; et al. (Nature Publishing Group, 2018)
To better understand host and immune response to diseases, gene expression studies require identification of reference genes with stable expression for accurate normalisation. This study describes the identification and testing of reference genes with stable expression profiles in koala lymph node tissues across two genetically distinct koala populations. From the 25 most stable genes identified in transcriptome analysis, 11 genes were selected for verification using reverse transcription quantitative PCR, in addition to the commonly used ACTB and GAPDH genes. The expression data were analysed using stable genes statistical software - geNorm, BestKeeper, NormFinder, the comparative ΔCt method and RefFinder. All 13 genes showed relative stability in expression in koala lymph node tissues, however Tmem97 and Hmg20a were identified as the most stable genes across the two koala populations.